ANALYSIS OF FIERSA BESARI SPEECH ACT ON YOUTUBE PLAYLIST “EPISODE SEBUAH JURNAL” PRAGMATIC STUDY - Yunanda, Yessy; Rahmat, Wahyudi; Samsiarni, Samsiarni; Rifai, Ali Al Bukhari Bin Mhd. (ppjbsip, 2021)
This study aims to analyze and describe the form of illocutionary speech used by Fiersa Besari in the social media Youtube. This study uses a descriptive method to achieve research objectives following the problem under study. This research with a qualitative approach uses the descriptive method. The data source used is the video in the “Episode of a Journal” playlist on the Fiersa Besari Youtube social media. This research data are fragments of words or sentences included in the type of illocutionary speech act. Based on the study results, it can be conveyed that the analysis of Fiersa Besari’s illocutionary speech acts in the “Episode of a Journal” playlist on Youtube social media serves to make the result of the illocutionary speech acts found in the video even better. The use of illocutionary speech acts in Fiersa Besari’s video in the “Episode of a Journal” playlist found four types of speech acts: assertive speech acts, directive speech acts, expressive speech acts, and commissive speech acts. The most common speech acts, while the least found, were commissive speech acts.